The fate of pollen in two morphologically contrasting buzz-pollinated Solanum flowers - Vasquez-Castro, Christian Ary; Morel, Elodie; Garcia-Simpson, Bernardo; Vallejo-Marín, Mario (Journal of Pollination Ecology, 2025)
Pollen transfer efficiency (PTE) and pollen deposition patterns on a pollinator’s body significantly influence plant reproductive success. However, studies on pollen fates (i.e., the destination of pollen grains after anther dehiscence) in animal-pollinated species offering pollen as the sole reward are limited. This study investigated pollen fates in two nectarless, buzz-pollinated Solanum species with contrasting floral morphology. Experimental trials were conducted involving one pollen donor and four recipient flowers of Solanum rostratum Dunal or S. dulcamara L., using captive Bombus terrestris L. as pollinators. The number of pollen grains remaining in the anthers, deposited on stigmas, placed on the pollinator, or falling to the ground was quantified. Both species produced a relatively high number of pollen grains as expected for buzz-pollinated plants. Pollen deposition curves followed exponential decay patterns, with a higher number of pollen grains deposited for S. dulcamara, and a similar rate of decline for both species. PTE was similar between species (0.86% vs. 1.00%, for S. rostratum and S. dulcamara, respectively) but these values could be 25% higher if we were to measure pollen deposition in 20 recipients rather than four as in the present study. Although both species had similar PTE values, their pollen fates differed: in S. rostratum, pollen was mainly lost to the ground, whereas in S. dulcamara, it was primarily removed by bee grooming, likely due to differences in their floral architectures. These findings suggest that species with different flower morphology could exhibit different pollen fates without impacting pollen transfer to conspecific stigmas.